Rudyard Kipling’s Kim as a Narrative of Empire - Baral, Pawan (THE ACADEMIA, 2025)
The paper seeks to examine Rudyard Kipling’s novel Kim in relation to British Empire in India. One way and another, all narrative elements revolve around and comply with the British rule in India. The paper employs textual narrative analysis to excavate how Kipling weaves the novel round the British empire in India. The adventure of the title character is central to the plot. He undertakes the adventure to search for a Red Bull on a green field, which is a regimental flag of the regiment to which Kim’s father once belonged. Kipling creates and projects Kim in such a way that he is not only entrapped but also works for colonial cause. During his adventurous quest, he instrumentalizes Teshoo Lama as a shield of innocence for his colonial expedition. In the meantime, Kim keeps on working for Colonel Creighton, who is the head of British intelligence agency. The Great Game gets dominant implication in the novel.